The relation of meaning to wording in Mandela’s speech of inauguration as President: A systemic functional analysis of rhetorical devices, marked syntax and appraisal - MarÃa MartÃnez Lirola (Journal of Modern Languages)
This article intends to analyse the main linguistic characteristics of one of Mandela’ speeches: the address to the nation at the inauguration of Nelson Mandela as President of the Republic of South Africa, Union Building, Pretoria, 10 May 1994. Having Systemic Functional Linguistics (hereafter SFL) and Critical Discourse Analysis as theoretical frameworks, this paper will explore the speech as an instance of the generalized system of meanings surrounding it by paying attention to the different rhetorical devices (parallelisms, enumerations, repetitions, and exclamations), to marked syntax, and to appraisal. This analysis will show how these resources allow the author to create a social reality through language, to contribute to the vividness of the speech, and to build the reality of the historical moment that the speech shows. Special attention will be given to the situational variable of tenor to describe the relationship that Mandela (the addressor) establishes with the audience (the addressee), to whom the speech is addressed to. The analysis will allow a conclusion that there is a clear relationship between language and meaning.